2020
DOI: 10.1101/2020.12.09.418830
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Segregating domain-general from emotional context-specific inhibitory control systems - ventral striatum and orbitofrontal cortex serve as emotion-cognition integration hubs

Abstract: Inhibitory control hierarchically regulates cognitive and emotional systems in the service of adaptive goal-directed behavior across changing task demands and environments. While previous studies convergently determined the contribution of prefrontal-striatal systems to general inhibitory control, findings on the specific circuits that mediate the context-specific impact of inhibitory control remained inconclusive. Against this background we employed an evaluated emotional Go/No Go task with fMRI in a large co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 85 publications
(134 reference statements)
1
12
0
Order By: Relevance
“…The conventional mass univariate activation and connectivity analyses revealed that AT1R blockade specifically attenuated left dlPFC reactivity and amygdala-vACC connectivity in response to fearful oddballs. The dlPFC represents a functionally heterogenous region and has been involved in several domains related to fear processing, including implicit and explicit cognitive regulation of negative affect and task-irrelevant distractors (Beauregard, Lévesque, & Bourgouin, 2001; Delgado, Nearing, LeDoux, & Phelps, 2008; Kim & Hamann, 2007; Lévesque et al, 2003; C. Liu et al, 2021; Ochsner, Bunge, Gross, & Gabrieli, 2002; Ochsner et al, 2004; Phan et al, 2004; Zhuang et al, 2021) rapid attention towards salient stimuli, including threat-related stimuli (Clarke et al, 2020; Peers, Simons, & Lawrence, 2013; Sagliano, D’Olimpio, Izzo, & Trojano, 2017) and the conscious subjective experience of emotional states including fear (Kroes et al, 2019; LeDoux & Pine, 2016). In accordance with this functional characterization of the dlPFC in neuroimaging studies lesion and non-invasive brain stimulation studies have provided more causal evidence for an involvement in the fear-related process.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional mass univariate activation and connectivity analyses revealed that AT1R blockade specifically attenuated left dlPFC reactivity and amygdala-vACC connectivity in response to fearful oddballs. The dlPFC represents a functionally heterogenous region and has been involved in several domains related to fear processing, including implicit and explicit cognitive regulation of negative affect and task-irrelevant distractors (Beauregard, Lévesque, & Bourgouin, 2001; Delgado, Nearing, LeDoux, & Phelps, 2008; Kim & Hamann, 2007; Lévesque et al, 2003; C. Liu et al, 2021; Ochsner, Bunge, Gross, & Gabrieli, 2002; Ochsner et al, 2004; Phan et al, 2004; Zhuang et al, 2021) rapid attention towards salient stimuli, including threat-related stimuli (Clarke et al, 2020; Peers, Simons, & Lawrence, 2013; Sagliano, D’Olimpio, Izzo, & Trojano, 2017) and the conscious subjective experience of emotional states including fear (Kroes et al, 2019; LeDoux & Pine, 2016). In accordance with this functional characterization of the dlPFC in neuroimaging studies lesion and non-invasive brain stimulation studies have provided more causal evidence for an involvement in the fear-related process.…”
Section: Discussionmentioning
confidence: 99%
“…Participants N=250 healthy right-handed participants were enrolled in the current study and underwent a validated Go/NoGo fMRI paradigm. The data has been previously used to examine undirected functional connectivity within domain-general and emotion-specific inhibitory brain systems (Zhuang et al, 2021) and was part of larger neuroimaging project examining pain empathy (Li et al, 2018;Zhou et al, 2020), emotional face memory (Liu et al, 2022) and mirror neuron processing (Xu et al, 2022). After quality assessment n=218 subjects were included (104 males, Supplementary Materials).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study we demonstrated that subjects exhibited more errors during inhibitory control (i.e., NoGo>Go) as well as faster responses in positive Go contexts and lower accuracy in positive NoGo contexts (Zhuang et al, 2021). Given that sex-differences were examined in the DCM model the present analyses additionally examined sex-differences on accuracy and reaction times (Supplementary Materials).…”
Section: Behavioral Data Analysismentioning
confidence: 97%
See 2 more Smart Citations